Designing a maintenance management system for a small to medium sized manufacturing plant - Drysdale, Gavin John (Not Specified, 2024)
[page 54, 55 missing] During the last three decades, technology has advanced at an incredible rate. Plants have become more automated and complex, and it is evident thet the quality of service provided by the maintenance department has become a cornerstone of profitability. The idea of a Maintenance Management System is not a new one and considerable research has been carried out on various facets of the subject. However, it appears that much of this research has been directed at large organisations. This thesis covers research which is aimed at small to medium-sized plants with limited resources, and which do not have a developed Maintenance Management System. The objectives of the research concern the iMplementation of a system which will: design and al enable engineering staff to attend to breakdowns and other work in a logical manner, which will increase the overall efficiency of the plant. bl control artisan hours effectively and reduce overtime hours worked cl maintain accurate service and history records dl reduce unnecessary stoppages and obtain optimum plant availability at the minimum possible cost e) improve the attitude of executive management towards maintenance policies and provide a safe working environment fJ identify unreliable machines which are uneconomical to maintain gJ encourage the use of maintenance manuals ( i i ) These objectives were achieved by designing a Management System which included the following: Maintenance 1. A Maintenance Work Order System. This system would ensure that all work was carried out effectively. It would also produce feedback on maintenance performance, costs and equipment history. 2. A Preventive Maintenance System. Such a system would be modest to begin with and could gradually become more comprehensive to include all production equipment. 3. A Maintenance Information System. The trend nowadays is toward computerization. Therefore, a simple computerbased system was designed which could manipulate data on equipment inventory and history records. The system could be expanded to suit individual requirements. 4. Pareto Analysis. This technique could be used to identify key areas needing special attention, such as high downtime costs. 5. Performance Indices. By collecting data related to cost and performance, it was demonstrated how these indices could be calculated and plotted regularly. The research enabled Management Bystem for the author a smal 1 to to design a medium sized Maintenance plant. The investigation and analysis of results demonstrated that Pareto Analysis could be used to identify critical equipment, while performance indices would be useful tools for analysing maintenance or production trends. The importance of selling this system to top management was emphasised, because the success of the system would depend on their complete acceptance. For the plant under investigation, a central maintenance organisation plan was recommended because of its flexibility. The benefits of contract maintenance, and it's limits, were also highlighted. This thesis makes a contribution to the field of maintenance management because it provides clear guidelines on how to desi~n a suitable Maintenance Management System to satisfy individual requirements.